Storage of sugarcane stalks (Saccharum officinarum cv. SP 79-1011) in low oxygen atmospheres and the effects on enzymatic browning - Schianoli Frateschi, Camila [UNESP]; Durigan, José Fernando [UNESP]; Omir Marques, Marcos [UNESP]; T.D. Hojo, Ellen [UNESP]; O. Santos, Leandra [UNESP]; Cunha Júnior, Luís Carlos; de Almeida Teixeira, Gustavo H. (Elsevier, 2013)
Although sugarcane consumption is very popular worldwide there are few studies regarding the postharvest storage of stalks that focus on controlling enzymatic browning. The objective of this study was to evaluate the quality of sugarcane stalks stored at 10±1°C in controlled atmosphere with various oxygen (O2) levels (1kPa, 5kPa, 10kPa, 15kPa, and 21kPa) and to verify the effect of this storage on the activities of polyphenoloxidase (PPO) and peroxidase (POD). At 1kPa and 5kPa O2, the stalks' respiratory rate, POD activity, and reducing sugar content were significantly less (P<0.05) than at higher O2 concentrations. In contrast, low O2 levels did not affect PPO activity or influence cane coloration. These results can be used to guide the choice of plastic films, making it possible to store sugarcane stalks in a controlled atmosphere. © 2013 Elsevier B.V.
Keywords: Enzymatic browning; Peroxidase; Polyphenoloxidase; Respiration; Sugarcane